Pelatihan Pembuatan Media Pembelajaran Toontastic 3D bagi Guru-guru di Madrasah - Anni Holila Pulungan; Joko Kusmanto; Hammi Kasifa Pohan; Andre Silitonga; Rahmadi (Ilin Institute, 2023)
The goal of this community service is to use Toontastic 3D to improve teachers' competency in teaching. The target audiences of this program are teachers at Madrasah Ibtidaiyah Ar Rasyid-Deli Serdang, who represent a variety of academic disciplines. The fundamental ideas and skills that teachers must have in order to become effective in Toontastic 3D animation design are explained utilizing the lecture technique. Demonstrations are given to provide attendees practical experience with the application. They are trained and assisted in using Toontastic 3D independently through workshops. A question and answer is also used to enable teachers to ask questions and discuss any difficulties they may have had while receiving the training. Training booklets are given to the teachers. They can create an interesting Toontastic tutorial videos that are relevant to their areas of study. Their ability to impart knowledge has improved, as has their comprehension of creating animated videos. Based on the findings, teachers are overwhelmingly pleased and enthused (90%) about this activity. The teachers' imaginations have soared, and they are happy with the instruction and direction given for the Toontastic 3D animation program.